2019
DOI: 10.1371/journal.pone.0224462
|View full text |Cite
|
Sign up to set email alerts
|

Foliar plasticity related to gradients of heat and drought stress across crown orientations in three Mediterranean Quercus species

Abstract: Studies on plasticity at the level of a single individual plant provide indispensable information to predict leaf responses to climate change, because they allow better identification of the environmental factors that determine differences in leaf traits in the absence of genetic differences. Most of these studies have focused on the responses of leaf traits to variations in the light environment along vertical gradients, thus paying less attention to possible differences in the intensity of water stress among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 63 publications
2
10
0
Order By: Relevance
“…The cork oak leaves in the trees of all the provenances showed a clear schlerophytic character ( Figure 1 and Figure 2 ) and their morphological features ( Table 1 ) were within the range of values reported for the species. Leaf sizes (4.6–6.8 cm 2 ) were similar to those reported by Mediavilla et al [ 28 ] for Q. suber leaves taken from different orientations in the canopy (5.5–7.4 cm 2 ) and the 7.1 cm 2 reported by Prats et al [ 20 ]. The specific leaf area values (55.6–67.8 cm 2 /g) were of the same order of magnitude as those obtained in adult leaves of Q. suber growing under contrasting environments and located in different positions and orientations of the canopy (50.0 to 126.0 cm 2 /g) [ 28 , 29 , 30 , 31 , 32 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The cork oak leaves in the trees of all the provenances showed a clear schlerophytic character ( Figure 1 and Figure 2 ) and their morphological features ( Table 1 ) were within the range of values reported for the species. Leaf sizes (4.6–6.8 cm 2 ) were similar to those reported by Mediavilla et al [ 28 ] for Q. suber leaves taken from different orientations in the canopy (5.5–7.4 cm 2 ) and the 7.1 cm 2 reported by Prats et al [ 20 ]. The specific leaf area values (55.6–67.8 cm 2 /g) were of the same order of magnitude as those obtained in adult leaves of Q. suber growing under contrasting environments and located in different positions and orientations of the canopy (50.0 to 126.0 cm 2 /g) [ 28 , 29 , 30 , 31 , 32 ].…”
Section: Discussionsupporting
confidence: 87%
“…In the present study, the observed amounts of the total chlorophyll, expressed per unit of leaf area or per unit of dry weight ( Table 1 ), were consistent with those reported in the available studies for Q. suber , for example, the results of Ramírez-Valiente et al [ 30 ] for leaves of open-pollinated trees from populations in Morocco, Portugal and Spain (2.68 mg/g, 2.64 mg/g and 2.74 mg/g respectively) and 55.7 µg/cm 2 and 56.0 µg/cm 2 total chlorophyll in sun and shade leaves of 40-year-old Q. suber trees [ 40 ]. Mediavilla et al [ 28 ] also observed that the chlorophyll content differed among canopy orientations, with lower values on the west side (80 vs. 110 µg/cm 2 ), probably due to a direct effect of excess radiation at the time of the day with highest leaf temperatures and lowest water potential on the west facing leaves.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on its magnitude and spatio‐temporal patterning, this subindividual phenotypic variance can have multiple ecological effects. These include optimizing the exploitation of limiting resources such as light, water or nitrogen (Osada et al ., 2014; Ponce‐Bautista et al ., 2017; Mediavilla et al ., 2019), altering the outcome of interactions with animals (Sobral et al ., 2013, 2014; Shimada et al ., 2015; Wetzel et al ., 2016), driving selection on reproductive traits (Austen et al ., 2015; Dai et al ., 2016; Arceo‐Gómez et al ., 2017; Kulbaba et al ., 2017), and enhancing tolerance of environmental unpredictability (Tíscar Oliver & Lucas Borja, 2010; Hidalgo et al ., 2016). Because of these ecological effects, subindividual variability can eventually influence the fitness of individuals and become itself a target for natural selection, since plants not only have characteristic trait means but also characteristic trait variances and spatio‐temporal patterns of subindividual heterogeneity (Herrera, 2009, 2017; Kulbaba et al ., 2017; Harder et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Depending on its magnitude and spatio-temporal patterning, this subindividual phenotypic variance can have multiple ecological effects. These include optimizing the exploitation of limiting resources such as light, water or nitrogen (Osada et al, 2014;Ponce-Bautista et al, 2017;Mediavilla et al, 2019), altering the outcome of . CC-BY-NC-ND 4.0 International license perpetuity.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on its magnitude and spatio-temporal patterning, this subindividual phenotypic variance can have multiple ecological effects. These include optimizing the exploitation of limiting resources such as light, water or nitrogen (Osada et al ., 2014; Ponce-Bautista et al ., 2017; Mediavilla et al ., 2019), altering the outcome of interactions with animals (Sobral et al ., 2013, 2014; Shimada et al ., 2015; Wetzel et al ., 2016), driving selection on reproductive traits (Austen et al ., 2015; Dai et al ., 2016; Arceo-Gómez et al ., 2017; Kulbaba et al ., 2017), and enhancing tolerance of environmental unpredictability (Tíscar Oliver & Lucas Borja, 2010; Hidalgo et al ., 2016). Because of these ecological effects, subindividual variability can eventually influence the fitness of individuals and become itself a target for natural selection, since plants not only have characteristic trait means but also characteristic trait variances and spatio-temporal patterns of subindividual heterogeneity (Herrera, 2009, 2017; Kulbaba et al ., 2017; Harder et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%